Proceedings: Arctic Transportation Infrastructure: Response Capacity and Sustainable Development (2012)
The Arctic Maritime and Aviation Transportation Infrastructure Initiative (AMATII) serves as an initial platform for inventorying critical assets in the Arctic’s aviation and maritime environment. The Initiative facilitates ongoing and increased communication and collaboration throughout the Circumpolar North. It serves as a coordination point for future research and has the potential to facilitate technology transfer within the Arctic region. AMATII builds on and responds to past efforts and projects of two working groups within the Arctic Council—the Protection of the Arctic Marine Environment’s 2009 Arctic Marine Shipping Assessment Report and the Sustainable Development Working Group’s Circumpolar Infrastructure Task Force (CITF), which hosted the Arctic Aviation Experts conferences in 2005 (Khanty-Mansiysk, Russia) and 2006 (Winnipeg, Manitoba, Canada). More directly, it follows on the strategic plan set forth at the 2010 Arctic Aviation Experts Conference (AAEC) in Fairbanks, Alaska.